FLOW INJECTION-FAAS DETERMINATION OF CHROMIUM, IRON, POTASSIUM AND SODIUM IN COMMERCIAL SWEETS WITH ON-LINE PRE-CONCENTRATION USING ION-EXCHANGE RESIN - Khokhar, M. Y.; Iqbal, J.; Niazi, S. B. (Journal of Research (Science), 2000)
An on-line pre-concentration method based on flow injection ion-exchange analysis combined with flame atomic absorption spectrometry has been developed for the determination of chromium, iron, potassium and sodium in commercial sweets. Cation-exchange resin microcolumn has been used for pre-concentration of metals. Effect of flow rate on the binding and elution and pH for binding and molarities of eluting buffers for Cr, Fe, K and Na has been investigated.